4-[4-(3-Methoxybenzamido)phenoxy]-N-methylpicolinamide - Na-Na Meng; Ting-Ting Huang; De-Kuan Li; Wen-Xin Zhang; Luo-Ting Yu (Acta Crystallographica Section E, 2010)
In the title compound, C21H19N3O4, the central benzene ring makes dihedral angles of 78.54 (6) and 75.30 (6)° with the pyridine and 3-methoxyphenyl rings, respectively. An intramolecular N—H...N interaction occurs, generating an S(?). The crystal packing shows intermolecular N—H...O hydrogen-bonding interactions between the N—H groups and the O atoms of the 3-methoxyphenyl ring and the carbonyl groups of the amide functions. Intermolecular C—H...O interactions are also present.